2024
DOI: 10.1186/s13068-023-02447-4
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial transformation of lignin: key enzymes and high-value products

Jinming Gu,
Qing Qiu,
Yue Yu
et al.

Abstract: Lignin, a natural organic polymer that is recyclable and inexpensive, serves as one of the most abundant green resources in nature. With the increasing consumption of fossil fuels and the deterioration of the environment, the development and utilization of renewable resources have attracted considerable attention. Therefore, the effective and comprehensive utilization of lignin has become an important global research topic, with the goal of environmental protection and economic development. This review focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 171 publications
0
1
0
Order By: Relevance
“…Research has reported urocanate hydratase activity in various bacterial species such as Pseudomonas putida [19], Mycobacterium smegmatis [20], and Bacillus subtilis [21]. Additionally, fungi like Serratia marcescens also exhibit urocanate hydratase activity [22]. The taxonomic range extends to mammalian tissues, including rat liver [23] and rabbit liver [24], emphasizing the importance of the histidine degradation pathway across different taxa.…”
Section: Discussionmentioning
confidence: 99%
“…Research has reported urocanate hydratase activity in various bacterial species such as Pseudomonas putida [19], Mycobacterium smegmatis [20], and Bacillus subtilis [21]. Additionally, fungi like Serratia marcescens also exhibit urocanate hydratase activity [22]. The taxonomic range extends to mammalian tissues, including rat liver [23] and rabbit liver [24], emphasizing the importance of the histidine degradation pathway across different taxa.…”
Section: Discussionmentioning
confidence: 99%